Cross-reaction of anti-simian immunodeficiency virus envelope protein antibodies with human immunoglobulins - (:unkn) unknown (WILEY, 2003)
It has been recently established that retroviral envelope proteins (REPs) have structural features similar to those of immunoglobulins (Igs). In this study, we asked whether anti-REP antibodies cross-react with human Igs (hIgs). To this end, murine monoclonal antibodies (mMoAbs) that had been raised against a simian immunodeficiency virus (SIV) envelope protein, SIVMac251gp120, were screened for their ability to react with human monoclonal Igs (HMIgs). We show that two HMIgs, RFSJ2 (a rheumatoid factor) and PAMLN6 (a human anti-hIg V region antibody), but not a number of other HMIgs, could be weakly, but consistently, bound by anti-SIVMac251gp120 mMoAbs KK17 and KK46, as judged by indirect enzyme-linked immunosorbent assay and a liquid-phase inhibition immunoassay. Both mMoAbs are specific to amino acid residues in the V3 loop of the SIVMac251gp120. The RFSJ2 Ig heavy-chain V region (V-H ) is coded in part by a human V-H gene, V-H 3-30.3 and includes the idiotope 7B4 (NKYY), which was previously shown to be present in the gp120 protein of a number of HIV-2 and SIV strains. However, an entirely different V-H gene codes the PAMLN6 V-H region, opening the possibility that epitope(s) shared between SIVMac251gp120 and hIgs may not be limited to the 7B4 idiotope.
Keywords: B-CELLS; V3 LOOP; BINDING; AUTOANTIBODIES; SEQUENCES; TYPE-1; REGION